Who gives wealth transfers to whom and when? Patterns in the giving and receiving of lifetime gifts and loans - Bee Boileau; David Sturrock (Institute for Fiscal Studies (IFS), 2023)
This report gives a new and up-to-date picture of the giving and receiving of significant intergenerational wealth transfers during life, summarising the findings of two research papers. New data from the Wealth and Assets Survey (WAS) allow us to build a comprehensive picture of the flow of wealth transfers made during life. The WAS asks about the giving and receiving of gifts and loans worth 500 or more between friends and family. We examine the change in patterns of giving over time, who gives and receives transfers, the contribution of these transfers to early-adult-life economic inequalities, and the events associated with giving and receiving wealth transfers during life.
Keywords: 330; Poverty; inequality and social mobility; Savings; pensions and wealth; Ageing; Housing; Inequality; Savings; Social mobility; Family; Wealth